ID2 controls differentiation of enteroendocrine cells in mouse small intestine. (17th January 2022) - Zinina, Valeriya V.; Ruehle, Frank; Winkler, Patricia; Rebmann, Lisa; Lukas, Hanna; Möckel, Stefanie; Diefenbach, Andreas; Mendez‐Lago, Maria; Soshnikova, Natalia
Abstract: Aims: The mammalian gut is the largest endocrine organ. Dozens of hormones secreted by enteroendocrine cells regulate a variety of physiological functions of the gut but also of the pancreas and brain. Here, we examined the role of the helix‐loop‐helix transcription factor ID2 during the differentiation of intestinal stem cells along the enteroendocrine lineage. Methods: To assess the functions of ID2 in the adult mouse small intestine, we used single‐cell RNA sequencing, genetically modified mice, and organoid assays. Results: We found that in the adult intestinal epithelium Id2 is predominantly expressed in enterochromaffin and peptidergic enteroendocrine cells. Consistently, the loss of Id2 leads to the reduction of Chromogranin A‐positive enteroendocrine cells. In contrast, the numbers of tuft cells are increased in Id2 mutant small intestine. Moreover, ablation of Id2 elevates the numbers of Serotonin + enterochromaffin cells and Ghrelin + X‐cells in the posterior part of the small intestine. Finally, ID2 acts downstream of BMP signalling during the differentiation of Glucagon‐like peptide‐1 + L‐cells and Cholecystokinin + I‐cells towards Neurotensin + PYY + N‐cells. Conclusion: ID2 plays an important role in cell fate decisions in the adult small intestine. First, ID2 is essential for establishing a differentiation gradient for enterochromaffin and X‐cells along the anterior‐posterior axis of the gut. Next, ID2 is necessary for the differentiation of N‐cells thus ensuring a differentiation gradient along the crypt‐villi axis. Finally, ID2 suppresses the commitment of secretory intestinal epithelial progenitors towards tuft cell lineage and thus controls host immune response to commensal and parasitic microbiota.